Schiff Base Derivatives of 2-Amino-2-deoxy-1,3,4,6-tetra-O-acetyl-b-D-glucopyranose - N. BEDEKAR, ATUL; N. NAIK, ADESH; C. PISE, ABHINAY (Asian Journal of Chemistry, 2010)
The present work deals with the synthesis of different Schiff bases of derivative of glucosamine. Schiff bases of glucosamine with salicylaldehyde or anisaldehyde could be easily synthesized. However Schiff bases of benzaldehyde and some other aldehydes could not be synthesized from glucosamine. Therefore glucosamine was converted to tetraacetyl derivative for synthesis of Schiff base. The amino group was protected during acetylation by converting it into Schiff base. The tetra-acetyl derivatives were also used to synthesize Schiff bases of benzaldehyde, 5-bromo-salicyaldehyde, vanillin and veratraldehyde. The product characterization was done with spectral analysis.